5(x-1)-2x=1

Simple and best practice solution for 5(x-1)-2x=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-1)-2x=1 equation:


Simplifying
5(x + -1) + -2x = 1

Reorder the terms:
5(-1 + x) + -2x = 1
(-1 * 5 + x * 5) + -2x = 1
(-5 + 5x) + -2x = 1

Combine like terms: 5x + -2x = 3x
-5 + 3x = 1

Solving
-5 + 3x = 1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 3x = 1 + 5

Combine like terms: -5 + 5 = 0
0 + 3x = 1 + 5
3x = 1 + 5

Combine like terms: 1 + 5 = 6
3x = 6

Divide each side by '3'.
x = 2

Simplifying
x = 2

See similar equations:

| y=2(-5)-1 | | x-3/8+2/5=4/5x | | 3ln(x+7)=-3 | | 5x^2+x=-9 | | x=w/10y | | 1/6-x=-2x-1/6 | | 8=4/X | | 36π=4/3πr^3 | | 4/9x1/4 | | 4/9*1/4 | | 9z^2+11=12z | | X^7+2X^5+5X^3=0 | | 2/3*2/3= | | (5x^3-4x)/(7x^3-2) | | 5x+-10=-15 | | 1/2x-1/8y=-1/4 | | x+x+0.04+0.40=10.35 | | 3/2x-11/2=-5/2 | | 9-4(3x+7)=2 | | x/4-8=x/5-6 | | 9x-14=32 | | 7/8-1/2= | | 8u^2-2u=o | | 2X-2=(X-5) | | 27=r^3 | | 6c+4d= | | 11=-3+2w | | Log^7(-3m-1)=log^7(-4m-6) | | -(1/3)y-6=-11 | | 8.9x+16.46=-11.1x+14.70 | | 4900((38950/4900)-X)=-770 | | 4900((38950/4900)-X)=770 |

Equations solver categories